2018
DOI: 10.1002/1878-0261.12314
|View full text |Cite
|
Sign up to set email alerts
|

Induced PTF1a expression in pancreatic ductal adenocarcinoma cells activates acinar gene networks, reduces tumorigenic properties, and sensitizes cells to gemcitabine treatment

Abstract: Pancreatic acinar cells synthesize, package, and secrete digestive enzymes into the duodenum to aid in nutrient absorption and meet metabolic demands. When exposed to cellular stresses and insults, acinar cells undergo a dedifferentiation process termed acinar–ductal metaplasia (ADM). ADM lesions with oncogenic mutations eventually give rise to pancreatic ductal adenocarcinoma (PDAC). In healthy pancreata, the basic helix‐loop‐helix (bHLH) factors MIST1 and PTF1a coordinate an acinar‐specific transcription net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 86 publications
1
19
0
Order By: Relevance
“…While this work was in progress, an independent study demonstrated that overexpression of Ptf1a in Panc1 cells could induce acinar-specific gene expression as well as inhibit clonogenic growth (Jakubison et al, 2018), whereas we find Panc1 to be Ptf1a resistant. The precise reason for this discrepancy is not known, but some differences in methodologies exist.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…While this work was in progress, an independent study demonstrated that overexpression of Ptf1a in Panc1 cells could induce acinar-specific gene expression as well as inhibit clonogenic growth (Jakubison et al, 2018), whereas we find Panc1 to be Ptf1a resistant. The precise reason for this discrepancy is not known, but some differences in methodologies exist.…”
Section: Discussionmentioning
confidence: 58%
“…The precise reason for this discrepancy is not known, but some differences in methodologies exist. For example, the approach of Jakubison et al (2018) may have achieved higher-level expression of Ptf1a, overcoming an inhibitory threshold not matched by our expression system. In addition, whereas we introduced Ptf1a via polyclonal lentiviral transduction, Jakubison et al (2018) employed stable plasmid transfection and clonal selection.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, mKIC cells exhibit an exclusive mesenchymal phenotype that is characterized by a fibroblastic morphology and high levels of Snail, MMP9 , and fibronectin ( FN1 ) expression. All these cancer cell lines are highly tumorigenic in orthotopic xenograft models …”
Section: Resultsmentioning
confidence: 99%
“…Our mouse model of acinar Kras mutation relies on loss of one Ptf1a allele, and this may also contribute to the inability of acinar-derived cells to undergo tumorigenesis. However, work from others indicates that loss of Ptf1a makes acinar cells more susceptible, not less susceptible, to tumorigenesis 33, 34. It is also unlikely that differences in Cre-mediated recombination in our acinar-derived and duct-derived cell models are responsible for the differences in carcinogenesis.…”
Section: Discussionmentioning
confidence: 78%